Capacitive Wireless Charging Technology in Wireless Electric Vehicle Battery Charging: Challenges and Opportunities - Razon, Chrizel; Abueva, Reyna (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2025)
This study aims to identify challenges, opportunities, and solutions related to capacitive wireless charging (Capacitive Power Transfer, CPT) technology in electric vehicles (EVs). The background of the study focuses on the need for efficient and environmentally friendly charging technology to support wider EV adoption. The methods include laboratory experiments to test electrode design, charging distance, and environmental conditions on power transfer efficiency. The results show that optimal electrode design and proper spacing and positioning can improve power transfer efficiency. However, temperature and humidity factors also affect system performance. In conclusion, CPT technology has great potential in supporting electric vehicle charging, although challenges still need to be overcome. The implications of this study are the need for further development in system design that is adaptive to environmental conditions and integration with smart grids to improve the efficiency and adoption of this technology.